Virtual Heritage: A Concise Guide 2021
DOI: 10.5334/bck.l
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Authenticity in Virtual Heritage

Abstract: This chapter examines why we wish to preserve heritage objects and practices via virtual heritage, and why the issue of authenticity is so important here but so seldom addressed. If we could give criteria to select and to create useful and even authentic-oriented virtual heritage projects, what would they be? Or are there methods and solutions out there waiting to be discovered?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Additionally, some criticism has emerged about international guidelines such as the London Charter and Seville Principles for having exhibited an excessive preoccupation with recreating the original as the primary determinant of cultural authenticity [40]. Instead, researchers have suggested that any definition of authenticity is itself based on evolving, often highly subjective criteria depending on different individual or collective opinions, cultural contexts, societal changes, and differing value systems that are impossible to define in a universal way [40][41][42]. Authenticity for many researchers, therefore, is not only about faithful representations of the past but also a much more dynamic process including (1) how these pasts are constructed, (2) the development of a virtual heritage project itself, and (3) the living experiences of those who are intended to find meaning in it [41].…”
Section: Authenticity In Virtual Reconstruction Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, some criticism has emerged about international guidelines such as the London Charter and Seville Principles for having exhibited an excessive preoccupation with recreating the original as the primary determinant of cultural authenticity [40]. Instead, researchers have suggested that any definition of authenticity is itself based on evolving, often highly subjective criteria depending on different individual or collective opinions, cultural contexts, societal changes, and differing value systems that are impossible to define in a universal way [40][41][42]. Authenticity for many researchers, therefore, is not only about faithful representations of the past but also a much more dynamic process including (1) how these pasts are constructed, (2) the development of a virtual heritage project itself, and (3) the living experiences of those who are intended to find meaning in it [41].…”
Section: Authenticity In Virtual Reconstruction Researchmentioning
confidence: 99%
“…Instead, researchers have suggested that any definition of authenticity is itself based on evolving, often highly subjective criteria depending on different individual or collective opinions, cultural contexts, societal changes, and differing value systems that are impossible to define in a universal way [40][41][42]. Authenticity for many researchers, therefore, is not only about faithful representations of the past but also a much more dynamic process including (1) how these pasts are constructed, (2) the development of a virtual heritage project itself, and (3) the living experiences of those who are intended to find meaning in it [41]. This understanding of authenticity shares UNESCO's reformulation of criteria for listing objects and sites as world heritage that was advanced in the Nara Conference of 1994 [43].…”
Section: Authenticity In Virtual Reconstruction Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Photogrammetry mainly involves the precise measurement of three-dimensional objects and terrain features from two-dimensional photos [ 1 ]. Topographical mapping, architecture, engineering, manufacturing, quality control, police investigation, defense, agriculture, geology, film and games industries are some of the areas where photogrammetry is used [ 2 ].…”
Section: Introductionmentioning
confidence: 99%